The Influence of Job Training, Work Discipline, and Communication on Employee Performance - Setyorini, Izni Nadah; Subarjo (LifeSciFi, 2025)
Employee performance is influenced by various factors, including job training, work discipline, and communication. This study aims to examine the effects of these factors on employee performance. A quantitative approach with an associative design was employed, involving 35 employees selected using a saturated sampling technique. Data were collected through an online questionnaire using a Likert scale. Analysis included validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination. The results show that job training does not have a significant effect on performance (p = 0.790), while work discipline (p = 0.044) and communication (p = 0.018) have positive and significant effects. Additionally, the F-test indicates that the three variables together significantly influence employee performance. The coefficient of determination suggests that other factors not examined may also play a role. The findings emphasize that work discipline and effective communication are key to improving employee performance, whereas job training requires further evaluation to maximize its impact.